2023
DOI: 10.7150/ijbs.78348
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IGF2BP1 attenuates renal injury and inflammation by alleviating m6A modifications and E2F1/MIF pathway

Abstract: Septic acute kidney injury (AKI) is characterized by inflammation. Pyroptosis often occurs during AKI and is associated with the development of septic AKI. This study found that induction of insulin-like growth factor 2 mRNA binding protein 1 (IGF2BP1) to a higher level can induce pyroptosis in renal tubular cells. Meanwhile, macrophage migration inhibitory factor (MIF), a subunit of NLRP3 inflammasomes, was essential for IGF2BP1-induced pyroptosis. A putative m6A recognition site was identified at the 3′-UTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…PLAT (plasminogen activator, tissue type) [325] and ALB (albumin) [326] might be involved in the occurrence and development of hypertension. BMI1 [327], AMH (anti-Mullerian hormone) [328], E2F1 [329], PF4 [330], VASH2 [331], GRIN1 [332], CYP11B2 [333], COMP (cartilage oligomeric matrix protein) [334], DES (desmin) [335], ANGPTL3 [336], CYP3A5 [337], DPEP1 [338], LRP2 [339], AGXT2 [340], FABP1 [341], SLC22A12 [342], CUBN (cubilin) [343], MIOX (myo-inositol oxygenase) [344], ARG2 [345], KHK (ketohexokinase) [346], CYP2C8 [347], SLC2A9 [348], GC (GC vitamin D binding protein) [349], VNN1 [350], NOX4 [351], EPHX2 [352], AKR1C3 [353], NR4A3 [354], PFKFB2 [355], SLC22A6 [356], F11 [357], SLC22A2 [358], AQP2 [171], EGF (epidermal growth factor) [359], KNG1 [360], SERPINA5 [361], KL (klotho) [362], ACE2 [363], NPNT (nephronectin) [364], SLC47A1 [358], MGAM (maltase-glucoamylase) [365], AQP3 [366], AZGP1 [367], GALNT3 [368], DPP4 [369], STC1 [370], ABCB1 [371], ERRFI1 [372], TREH (trehalase) [373], MANBA (mannosidase beta) [374], ERBB4 [375], VCAM1 [376] and ALB (albumin) [377] might play an important role in the pathophysiology of AKI. BMI1 [378], IGF2 [379], PRKCB (protein kinase C beta) [380], CCL5 [381], E2F1 [382], PF4 [111], CYP11B2 [383], WNT3A [384], COMP (cartilage oligomeric matrix protein) [385], DES (desmin) [335], ANGPTL3 [386], CYP3A5 [387], LRP2 [388], PAH (phenylalanine hydroxylase) [389], HMGCS2 [390]...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLAT (plasminogen activator, tissue type) [325] and ALB (albumin) [326] might be involved in the occurrence and development of hypertension. BMI1 [327], AMH (anti-Mullerian hormone) [328], E2F1 [329], PF4 [330], VASH2 [331], GRIN1 [332], CYP11B2 [333], COMP (cartilage oligomeric matrix protein) [334], DES (desmin) [335], ANGPTL3 [336], CYP3A5 [337], DPEP1 [338], LRP2 [339], AGXT2 [340], FABP1 [341], SLC22A12 [342], CUBN (cubilin) [343], MIOX (myo-inositol oxygenase) [344], ARG2 [345], KHK (ketohexokinase) [346], CYP2C8 [347], SLC2A9 [348], GC (GC vitamin D binding protein) [349], VNN1 [350], NOX4 [351], EPHX2 [352], AKR1C3 [353], NR4A3 [354], PFKFB2 [355], SLC22A6 [356], F11 [357], SLC22A2 [358], AQP2 [171], EGF (epidermal growth factor) [359], KNG1 [360], SERPINA5 [361], KL (klotho) [362], ACE2 [363], NPNT (nephronectin) [364], SLC47A1 [358], MGAM (maltase-glucoamylase) [365], AQP3 [366], AZGP1 [367], GALNT3 [368], DPP4 [369], STC1 [370], ABCB1 [371], ERRFI1 [372], TREH (trehalase) [373], MANBA (mannosidase beta) [374], ERBB4 [375], VCAM1 [376] and ALB (albumin) [377] might play an important role in the pathophysiology of AKI. BMI1 [378], IGF2 [379], PRKCB (protein kinase C beta) [380], CCL5 [381], E2F1 [382], PF4 [111], CYP11B2 [383], WNT3A [384], COMP (cartilage oligomeric matrix protein) [385], DES (desmin) [335], ANGPTL3 [386], CYP3A5 [387], LRP2 [388], PAH (phenylalanine hydroxylase) [389], HMGCS2 [390]...…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 [265], BMI1 [260], VCAM1 [321], AGTR1 [64], hsa-mir-638 [790], hsa-mir-221 [791], FOXC1 [792], YY1 [793], STAT3 [794] and BRCA1 [795] provided a clear picture of the prognosis of patients with hypertension. E2F1 [329], BMI1 [327], VCAM1 [376], USF2 [796], YY1 [797], STAT3 [798] and BRCA1 [799] have always been found in AKI. Identified E2F1 [382], BMI1 [378], VCAM1 [421], AGTR1 [87], MEF2A [800] and STAT3 [798] as a biomarkers for chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…METTL3, a crucial component of the m6A methyltransferase complex, serves as an active contributor to m6A methylation modifications and participates in immune responses across various diseases, such as breast cancer, infection, and kidney injury [ [23] , [24] , [25] , [26] ]. Within this investigation, a marked decrease in METTL3 expression was observed in the T2 asthma cohort as compared to the normal control group at the clinical, cellular, and animal levels.…”
Section: Discussionmentioning
confidence: 99%
“…IRF2 inhibition reduced the levels of inflammatory factors (IL-1β, IL-18, IL-6, and TNF-α), decreased the expression of Caspase-4 and GSDMD, and improved the survival rate of IRF2−/− mice after CLP. It was suggested that IRF2 deficiency inhibits inflammation and pyroptosis by inhibiting nonclassical inflammasomes [57]. The matrix glycoprotein thrombospondin-1 and upstream stimulatory factor 2 are also highly expressed in SA-AKI patients.…”
Section: Ischemia-reperfusion Injury Akimentioning
confidence: 99%
“…In vitro MIF knockdown reduced NLRP3 inflammasome-mediated pyroptosis in LPS-damaged HK-2 cells [ 55 ]. Pyroptosis also occurred in renal tubular cells with increased insulin-like growth factor 2 mRNA binding protein 1 [ 56 ].…”
Section: Ischemia-reperfusion Injury Akimentioning
confidence: 99%